Determinants of construction industry profitability in Malaysia - Lim, Tze Yin (Universiti Malaysia Sarawak (UNIMAS), 2013)
In most of the countries, the construction sector contribution in the national income is said to be significant has contributed to 40% to 60% towards the Gross Fixed Capital formation as well in developing countries (Wibowo, 2009). The Malaysia construction sector is divided into two part (Report from Market Watch 2012). One part is consisted of engineering works for instance civil engineering and other construction works such as construction for residential areas and commercial buildings as well. Apart from this, special commercial and works such as metal works, electrical works, plumbing, sewerage and sanitary works and others will be the another part in construction sector. In Malaysia, the construction sector has a place as the 3rd biggest provider to country income and has contributed to GOP (Gross Domestic Product) of the country (Bakar, Awang, Yusof & Adamy, 2011). Researches and economist have stated that the construction industry is a one of the productive sector which contributes to the Gross Domestic Product (GOP) of the country and has held market size about RM 43 billion based on gross output (Fong, 2005). Apart from this, research that performed by Dlamini (2012), has argue that the construction industry plays main role in economic growth. The study has proved that the industry is positively responsive towards the development of the country. Apart from this, the construction output has brought significant impact towards Gross Domestic Product (GOP) of a country.